2018
DOI: 10.1108/jima-11-2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

Muslim tourist perceived value: a study on Malaysia Halal tourism

Abstract: Purpose This study aims to align the theoretical foundations of Halal tourism to conventional tourism paradigms. It investigates Muslim tourists’ perception of value in the context of tourist destinations in Malaysia. Design/methodology/approach The partial least square structural equation modelling uses SMART–PLS for 170 Muslim tourists and uses a positive research approach with a quantitative basis of enquiry. Six variables of Muslim tourist perceived value, such as price, social, emotion and quality, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 46 publications
0
81
0
9
Order By: Relevance
“…There are many studies that demonstrate the importance of the availability of halal food for Muslims when it comes to choosing their tourism destinations [21,[90][91][92][93]. Several countries are therefore working to satisfy that requirement by promoting and disseminating their Muslim-friendly offerings through online channels aimed at the Muslim market segment, such as websites and applications, in order to ensure that their messages reach Muslim tourists [94].…”
Section: Criteria For Evaluating Destinations As Muslim-friendlymentioning
confidence: 99%
“…There are many studies that demonstrate the importance of the availability of halal food for Muslims when it comes to choosing their tourism destinations [21,[90][91][92][93]. Several countries are therefore working to satisfy that requirement by promoting and disseminating their Muslim-friendly offerings through online channels aimed at the Muslim market segment, such as websites and applications, in order to ensure that their messages reach Muslim tourists [94].…”
Section: Criteria For Evaluating Destinations As Muslim-friendlymentioning
confidence: 99%
“…Halal is a compulsory choice for Muslims, which does not only cover food matters. Therefore, the development of Halal Tourism destinations must be guided by teachings and principles in accordance with Islamic law; this includes all aspects of tourism activities [2]. Interpret halal as whatever is permitted in Islam.…”
Section: Halal Tourism Conceptmentioning
confidence: 99%
“…Halal Tourism plays an essential role in economic growth because it is able to create millions of jobs to increase national income [1][2][3]. Indonesia is making a lot of revenue from the Halal Tourism sector.…”
Section: Introductionmentioning
confidence: 99%
“…One of these areas is halal tourism, targeting Muslim travelers from around the world. Halal tourism, as opposed to conventional tourism, provides options for Muslim travelers, who prefer to travel without worrying about violating Shariah law [2] and have shown that it is a major country in halal tourism by becoming a tourist destination for Middle Easterners. Similarly, Indonesia is also passionate about introducing halal tourism in providing halal tourism, the government, through the Ministry of Tourism, designating several regions as a halal tourism destination.…”
Section: Introductionmentioning
confidence: 99%